2015
DOI: 10.1111/hiv.12280
|View full text |Cite
|
Sign up to set email alerts
|

The influence of patient beliefs and treatment satisfaction on the discontinuation of current first‐line antiretroviral regimens

Abstract: Patients' beliefs and satisfaction with therapy influence the durability of the first antiretroviral regimen. These patient-related factors modulate the impact of mild adverse events, and could explain differences in the rate of discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…Converging evidence suggests that the occurrence of unwanted adverse events during drug treatment is in part determined by nonpharmacological effects [17]. On the patient's side, it has been shown that beliefs and satisfaction with therapy modulate the impact of mild AEs on the discontinuation of antiretroviral regimens [18]. Nonpharmacological effects may explain our findings as well as the large differences in the ‘real-world’ reported to date for DTG.…”
Section: Discussionmentioning
confidence: 70%
“…Converging evidence suggests that the occurrence of unwanted adverse events during drug treatment is in part determined by nonpharmacological effects [17]. On the patient's side, it has been shown that beliefs and satisfaction with therapy modulate the impact of mild AEs on the discontinuation of antiretroviral regimens [18]. Nonpharmacological effects may explain our findings as well as the large differences in the ‘real-world’ reported to date for DTG.…”
Section: Discussionmentioning
confidence: 70%
“…It has been shown that patients' beliefs and satisfaction with therapy modulate the impact of mild AEs . However, in most patients (including women and older patients) who discontinued dolutegravir, the subsequent ART regime was well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…These results are reassuring for the long-term efficacy of the single tablet regimen as there is an association between satisfaction of HIV-infected patients with their treatment and compliance with cART [19,20]. We cannot exclude perception bias as patients' perception, even before switching, and personal beliefs can modulate and influence the perceived efficacy of new treatment, health improvement, and adverse events, translating into higher satisfaction with the new therapy [21]. Our results are in accordance with those of the randomized STRIVIING study, where virologically suppressed patients who switched for abacavir/lamivudine/dolutegravir were more satisfied with their treatment at week 24 compared with patients who did not change treatment [12].…”
Section: Discussionmentioning
confidence: 91%